Effect of more than one related auxiliary trait on estimation of heritability of herd life - Asif Jquebau, Mir; Kumar Paul, Amrit (The Indian Journal of Animal Sciences, 2011)
Culling of a dairy animal is an important character in dairy cattle breeding, which is influenced by production as well as auxiliary traits. One approach to get true estimate ofheritability of herd life (stayability) by adjusting production was reported in literature. Here it is seen that though they observed significant effect of production on the estimates and their standard errors there is more scope of obtaining true estimate by adjusting for production as well as other related auxiliary traits, It is seen that this technique also improves the standard errors.